In vitro antitumoral activity of Prosopis juliflora in front of melanoma type cancerogen cells - Cavalcante, Giani Maria (2021)
The aim of this study was to investigate the antitumor activity of Prosopis juliflora against human tumor cells of the B16-F10 lineage (melanoma) to search for new drugs derived from natural sources. In vitro tests were conducted with the crude extracts of leaves and stem bark against the tumor cell lines B16-F10 through the cytotoxicity test using MTT (3- (4,5-dimethiazol-2yl) 2,5-diphenyl tetrazolium of bromide) by monitoring after 24 and 48 h of exposure of tumor and non-tumor cells to different concentrations of the extracts (100; 50; 25; 12.5 μg/mL). The cytotoxicity tests were performed using non-tumor cells (macrophages lineage J744). The stem bark extract and the leaf extract of P. juliflora inhibited the proliferation of B16-F10 cells from the lowest tested concentration 12.5 Mg / ml and did not show cytotoxicity against non-tumor cells. However, P. juliflora leaf extract showed a considerable decrease in antineoplastic activity from 50 mg / ml. It is suggested the chemical study for the extraction and isolation of active compounds from the extract of the leaves and stem bark of P. juliflora, and through testing these compounds in vitro and in vivo to investigate their possible antitumor activity.